2014
DOI: 10.1007/s00253-014-5973-3
|View full text |Cite
|
Sign up to set email alerts
|

Membrane permeabilization underlies the enhancement of extracellular bioactivity in Shewanella oneidensis by a membrane-spanning conjugated oligoelectrolyte

Abstract: A stilbene-based membrane spanning conjugated oligoelectrolyte 4,4'-bis(4'-N,N-bis(6"-(N,N,N-trimethyl ammonium) hexyl) amino)-styryl) stilbene tetraiodide (DSSN+) has been reported to be able to interact with bacterial cells and enhance their bioelectricity generation in bioelectrochemical devices, although the mechanism remains elusive. The goal of this study was to elucidate the impacts of DSSN+ on extracellular bioactivity and the underlying mechanism. Specifically, extracellular ferrihydrite reduction by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 57 publications
0
38
0
Order By: Relevance
“…Also, a 1 μM concentration corresponds to a value near the lower end of the range of functional concentrations examined in the literature. [8][9][10][11] Negative charge was introduced to the supported bilayers by adding cholic acid at different concentrations to the membrane during casting, as shown in Figure 4. Cholic acid is a moderately hydrophilic molecule that is negatively charged near neutral pH and which incorporates near the hydrophilic headgroups of phospholipid membranes promoting side chain disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Also, a 1 μM concentration corresponds to a value near the lower end of the range of functional concentrations examined in the literature. [8][9][10][11] Negative charge was introduced to the supported bilayers by adding cholic acid at different concentrations to the membrane during casting, as shown in Figure 4. Cholic acid is a moderately hydrophilic molecule that is negatively charged near neutral pH and which incorporates near the hydrophilic headgroups of phospholipid membranes promoting side chain disorder.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting ltrates were probed for extracellular ALP activity by monitoring conversion of non-uorescent 4-methylumbelliferyl phosphate (MUP) to uorescent 4-methylumbelliferone (4-MU). 30,34,35 The uorescence intensity linearly increased over 60 min for ltrates from both unstained, untreated (UT) and DSSN+ treated cells (selected examples are shown in Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…10,15,21,22 Despite its utility, the origin of DSSN+ improvement in bioelectrochemical devices remains under debate. 9,10,17,21,[23][24][25][26][27][28][29][30] Model membrane studies have shown that COEs increase ion conductance across the membrane. 13 To add to mechanistic complexity, recent results suggest that COEs may interact with other components in the cell envelope, such as lipopolysaccharides and cholic acid.…”
mentioning
confidence: 99%
“…Samples collected from chambers with biofilm A and C were filtered through 0.20 μm filters (Pall Corporation, Singapore) before acetate quantification using HPLC (Shimadzu, Singapore) as described in previous work [19,20].…”
Section: Electrochemical and Biochemical Analysismentioning
confidence: 99%